STATE OF THE ART REVIEW: THE EFFECTIVENESS OF IMPLEMENTING PROBLEM BASED LEARNING (PBL) MODELS IN IMPROVING SCIENCE LEARNING - Wulandari, Titis; Tanjung, Yul Ifda; Karlinda; Yohandri; Abdul Razak (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
The problem based learning model is a student centered learning strategy, which is an innovative that learning model provides active learning conditions . this study aims to measures the effectiveness of research articles on the application of the PBL model to improving science learning. this type of research is a meta- analysis using secondary and quantitative data to draw accurate conclusion in the form of effectiveness by searching the literature from the EBSCO database, Google Scolar and Taylor & Francis. Articles that have been published from 2019-2023. The keywords for cross - sectional studies are as follows: "Problem based learning " and " education " and " science learning outcomes ". The articles studied were full text articles with an observational research design. The articles were collected using the PRISMA diagram, and analyzed using the Reviews Manager 5.3 applications. Based on the results of the Forest Plot of 4 articles on learning with the application of the PBL Model, it has 1.09 units higher to get good learning outcomes compared to students who are given the application of the non PBL model (P<0.001; 95% Ci: 0.29 – 1.89; I2 = 94%).